Is implantation of autologous chondrocytes superior to microfracture for articular-cartilage defects of the knee? A systematic review of 5-year follow-up data. (August 2019) - Na, Yuyan; Shi, Yuting; Liu, Wanlin; Jia, Yanbo; Kong, Lingyue; Zhang, Ting; Han, Changxu; Ren, Yizhong
Abstract: Background: Autologous chondrocyte implantation (ACI) and microfracture are two of the main surgical treatment options for articular cartilage lesions of the knee. Consensus regarding the best clinical options to repair knee cartilage lesions is lacking. We undertook a systematic review to clarify the clinical efficacy of ACI and microfracture at minimum mean 5-year follow-up. Methods: A literature search was conducted using the MEDLINE, Embase and Cochrane Library databases up to August 2018. Only comparative clinical studies of ACI and microfracture for the treatment of articular cartilage lesions of the knee with level I/Ⅱ evidence were included. Clinical outcomes and the prevalence of treatment failure from each study were extracted and compared. The methodological quality of the included studies was analyzed by means of the PEDro scale. Results: Five comparative studies (three randomized controlled trials and two prospective cohort studies) met our eligibility criteria. ACI and microfracture elicited significant improvement in clinical outcomes after 5 years. However, better clinical results with significant differences were found with modified versions of ACI (ACI with a modified collagen membrane [ACI-C] or matrix-applied chondrocyte implantation [MACI]) than with microfracture as determined by the Knee Injury and Osteoarthritis Outcome Score, activities of daily living assessment, Tegner Activity Scale score, and the International Knee Documentation Committee objective and subjective scores. No significant difference was observed in the treatment failure rate between these two methods within a particular study. Conclusions: Currently, the best-available evidence suggests that some clinical outcomes of articular cartilage lesions of the knee treated with modified versions of ACI (ACI-C or MACI) can significantly improve patient outcomes at the mid-term follow-up of 5 years compared with those obtained using microfracture. Highlights: Both ACI and microfracture elicited significant improvement in clinical outcomes after 5 years. Better clinical results with significant differences were found for KOOS and IKDC objective and subjective scores, with modified versions of ACI (ACI-C or MACI) than those obtained using microfracture.